Microstructural stability on aging of an α + β titanium alloy: Ti-6Al-1.6Zr-3.3Mo-0.30Si - Singh A.K.; Roy T.; Ramachandra C. (My University, 2025)
The development of the microstructure on aging of an (α + β) type titanium alloy containing 6A1-1.6Zr-3.3Mo-0.3Si (VT9) (in weight percent) has been studied. The β-transus temperature of this alloy is approximately 1243 K. Solution treatment in the β-phase field of the alloy followed by quenching in water at room temperature resulted in the formation of a single-phase martensite structure. The martensitic structure was confirmed to be orthorhombic (α″) using X-ray diffraction. The water-quenched (WQ) specimens were subjected to aging treatments at temperatures of 823, 873, and 973 K for various lengths of time. Aging at 823 K for times between 24 and 100 hours did not bring about any noticeable change in the microstructure. Aging at 823 K for 200 and 300 hours resulted in the heterogeneous precipitation of s2 suicide particles and thin films of β sandwiched between the interplatelet boundaries of martensite. .Electron diffraction analysis confirms that the crystal structure of suicide particles is hexagonal with lattice parameters a = 0.70(1) nm and c = 0.36(8) nm. Aging at 873 K for 12 and 24 hours resulted only in the precipitation of s2 suicide particles, while aging at the same temperatures for longer times (48, 100, and 200 hours) and also at 973 K for 6 to 100 hours resulted in the precipitation of silicides and also thin films of β and acicular martensite. The relative sizes of suicide precipitates and width of thin films of β phase increase with increasing aging time. The sites for suicide precipitation are mainly at α′-α′ boundaries, α-β interfaces, and sometimes within regions of transformed β. The kinetics of s2 suicide precipitation in this alloy is faster than in commercial near-α titanium alloys. This is attributed to the presence of Mo, a strong β stabilizer.